Development and Optimization of Metformin Hydrochloride Loaded Hydrogel Microspheres Prepared with Natural Polymers - Sharma, Dr. H. K. (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: Natural materials have advantages over synthetic materials as pharmaceuticals because they are nontoxic, less expensive, and easily available. Furthermore, they can be modified to obtain customized materials for drug delivery systems better or equivalent to synthetic products that are commercially available. The present investigation aimed at the optimization of controlled release hydrogel microsphere of metformin hydrochloride prepared with bora rice flour (BRF), mucilage of Dillenia indica fruits, and mucilage of Abelmoschus esculentus in combination. Materials and Methods: Physical, mucoadhesive, and in vitro drug release properties were studied. Validation of the optimization process, selection of optimized batch, and stability study of optimized batch were also among the objectives of this study. The response surface approach was used for optimization process. The experimental values were compared with the predicted values, and percentage errors were calculated. Results and Discussion: In the statistical optimization process, the models for the selected response variables were significant. It was observed that there was variable influence of the concentration of the independent variables (BRF and mucilage) on the responses. Mucilage exhibited pronounced effect on the properties of microspheres than BRF. However, the observed effect was the resultant effect of the influence of individual variables on microspheres. Conclusion: In this study, much deviation was not of the experimental values from the predicted values